Better use of inhaled medication in asthma and COPD through training, preparation and counselling: the On TRACk study protocol for a cluster randomised controlled trial. Issue 9 (6th September 2022) - Paske, R te; van Dijk, Liset; Linn, Annemiek J; van Boven, Job F M; Koster, Ellen S; Vervloet, Marcia
Abstract : Introduction: About 70% of patients with asthma and/or chronic obstructive pulmonary disease (COPD) use their inhaled medication incorrectly, leading to reduced disease control, higher healthcare use and costs. Adequate guidance from the pharmacy team from first dispense onwards can benefit patients in the long run. We propose an intervention ('On TRACk') to improve medication adherence and inhaler technique of adult patients with asthma and/or COPD. This intervention focuses on training pharmacy technicians (PTs) in patient-centred communication and inhalation instruction skills. In addition, patients are actively involved in refill consultations at the pharmacy. The aim of this study is to improve inhaler technique and better inhaled medication adherence among patients with asthma and/or COPD. This paper describes the study protocol. Methods and analysis: A cluster randomised controlled trial (RCT) with an intervention and control group of 15 pharmacies each will be conducted. Per intervention pharmacy, two PTs will be trained online. Each PT will include five patients who will prepare their second and third dispense counselling sessions by selecting three topics they wish to discuss. Pharmacies in the control cluster provide usual care. In total, 300 patients (150 per group) will be included. Up to 12 months after inclusion, patients complete 3-monthly follow-up questionnaires. Both a process evaluation and a cost-effectiveness analysis will be performed alongside the trial. Trial effectiveness on the patient level will be evaluated after the 12-month follow-up period. Patient data will be collected through questionnaires and pharmacy refill data. Patients' inhaler technique will be visually assessed by PTs. Semistructured interviews with PTs and patients will be conducted regarding implementation and fidelity. Direct and indirect health costs will be collected to assess cost-effectiveness. The primary outcome is adherence to inhalation maintenance medication measured with pharmacy refill data. Secondary outcomes are inhaler technique, persistence, patients' attitudes towards medication, self-efficacy in medication use and communication with their PTs. Ethics and dissemination: The study was approved by the Vrije Universiteit Amsterdam Ethics Committee (number: 2020.358). Results will be presented at (inter)national conferences and published in peer-reviewed journals. If proven to be (cost-)effective, the intervention should be considered for reimbursement and implementation in Dutch community pharmacies. Trial registration number: NL9750.